2004
DOI: 10.1071/sr03078
|View full text |Cite
|
Sign up to set email alerts
|

Soil properties in and around acid sulfate soil scalds in the coastal floodplains of New South Wales, Australia

Abstract: Soil profiles in 10 persistently bare areas (i.e. scalds), mainly located in coastal backswamps of New South Wales, Australia, were examined for chromium-reducible sulfur content and selected chemical properties. At 5 of the sites, the adjacent paddocks with vegetation cover were also examined. All of the tested sites had been affected by the extensive drainage of the surrounding acid sulfate soil (ASS) landscapes and the consequent oxidation of pyrite. All sites had low pH values in the surface soil layers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Pyrite formation can be rapid in natural inter-tidal environments (Howarth, 1979). Both pyrite and monosulfides are known to reform in CLASS landscapes due to seasonal shifts in hydrology or the formation of localised, highly reducing sub-environments Rosicky et al, 2004;Burton et al, 2006Burton et al, , 2007. Portnoy and Giblin (1997a) demonstrated that saturating a drained and acidified former saltmarsh with seawater stimulated both Fe(III) and SO 4 2− reduction.…”
Section: Introductionmentioning
confidence: 98%
“…Pyrite formation can be rapid in natural inter-tidal environments (Howarth, 1979). Both pyrite and monosulfides are known to reform in CLASS landscapes due to seasonal shifts in hydrology or the formation of localised, highly reducing sub-environments Rosicky et al, 2004;Burton et al, 2006Burton et al, , 2007. Portnoy and Giblin (1997a) demonstrated that saturating a drained and acidified former saltmarsh with seawater stimulated both Fe(III) and SO 4 2− reduction.…”
Section: Introductionmentioning
confidence: 98%
“…Extensive scalded areas with low pH commonly occur on these coastal floodplains after extended dry periods and hydrous Fe oxides and oxyhydroxides can accumulate rapidly via upward evaporative flux of metal-bearing porewaters (Rosicky et al, 2004). These scalded areas can also accumulate high concentrations of soluble and exchangeable trace metals and can potentially act as a large source to overlying waters following seawater inundation, as demonstrated in this study.…”
Section: Role Of Fe Oxyhydroxide Mineralsmentioning
confidence: 82%
“…Rosicky et al, 2004). While the areal extent of these scalded areas may be small, the results indicate that these areas can potentially contribute high concentrations of acidity and trace metals to overlying surface waters when inundated.…”
Section: Implications For Sea-level Rise and Storm Surge Eventsmentioning
confidence: 91%
See 2 more Smart Citations